2010
DOI: 10.5194/cp-6-229-2010
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the last glacial cycle with a coupled climate ice-sheet model of intermediate complexity

Abstract: Abstract.A new version of the Earth system model of intermediate complexity, CLIMBER-2, which includes the three-dimensional polythermal ice-sheet model SICOPOLIS, is used to simulate the last glacial cycle forced by variations of the Earth's orbital parameters and atmospheric concentration of major greenhouse gases. The climate and icesheet components of the model are coupled bi-directionally through a physically-based surface energy and mass balance interface. The model accounts for the time-dependent effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
261
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 185 publications
(277 citation statements)
references
References 47 publications
14
261
1
1
Order By: Relevance
“…As was shown by Ganopolski et al (2010), simulation of a complete glacial termination, even with the prescribed GHG forcing, is only possible when the deposition of glaciogenic dust is taken into account. This is even more important in the case of a constant CO 2 concentration.…”
Section: Experiments With Constant Comentioning
confidence: 99%
See 4 more Smart Citations
“…As was shown by Ganopolski et al (2010), simulation of a complete glacial termination, even with the prescribed GHG forcing, is only possible when the deposition of glaciogenic dust is taken into account. This is even more important in the case of a constant CO 2 concentration.…”
Section: Experiments With Constant Comentioning
confidence: 99%
“…As discussed by Ganopolski et al (2010), both the magnitude and temporal dynamics of the simulated glacial cycles are very sensitive to the choice of model parameters, in particular, related to surface mass balance, basal sliding, and glaciogenic dust. It was also shown that without enhanced dust deposition, complete deglaciation is not achieved in the model.…”
Section: Baseline Experimentsmentioning
confidence: 99%
See 3 more Smart Citations